On the Mechanism of Cuprate Crystal Growth: The Role of Mixed Metal Carbonates. (25th June 2015) - Green, David C.; Boston, Rebecca; Glatzel, Stefan; Lees, Martin R.; Wimbush, Stuart C.; Potticary, Jason; Ogasawara, Wataru; Hall, Simon R.
Abstract : The mechanism of formation of the superconductor Bi2 Sr2 CaCu2 O8+ x (Bi‐2212) has been an open question since its discovery in 1988. By controlling crystal growth through the use of biopolymers as multivalent cation chelating agents, it is demonstrated through X‐ray diffraction and thermogravimetric analysis, that it is the formation of a mixed metal carbonate eutectic that promotes the formation of the target phase. X‐ray diffraction experiments, supported by infrared spectroscopy, identify this phase as (Sr1− x Ca x )CO3 . This knowledge allows to further reduce the eutectic melting point by the incorporation of a biopolymer rich in potassium ions, resulting in the scalable formation of Bi‐2212 at a temperature 50 °C lower than has been achieved previously. Abstract : The precise mechanism of formation of the superconductor Bi2 Sr2 CaCu2 O8 +x (Bi‐2212) is unknown. Via extensive X‐ray diffraction, infrared spectroscopy, and thermogravimetric analysis, the mechanism is identified, and it is found that a carbonate eutectic (Sr1− x Ca x )CO3 is the key driver in the formation of Bi‐2212. The introduction of potassium ions leads to the formation of Bi‐2212 at a temperature 50 °C lower than that achieved previously.